The generator coordinate method for a reaction coordinate coupled to a harmonic oscillator bath - Cruz, FFDS; Ruzzi, M. [UNESP]; Schmidt, ACK (American Institute of Physics (AIP), 1998)
This paper investigates the usefulness of the generator coordinate method (GCM) for treating the dynamics of a reaction coordinate coupled to a bath of harmonic degrees of freedom. Models for the unimolecular dissociation and isomerization process (proton transfer) are analyzed. The GCM results, presented in analytical form, provide a very good description and are compared to other methods Like the basis set method and multiconfiguration time dependent self-consistent field. (C) 1998 American Institute of Physics. [S0021-9606(98)50934-8].